Uma avaliação de toolkits para criptografia baseada em emparelhamento bilinear - Sampaio, Frederico M. B.; Grossi, Lucas Goulart; Maia Neto, Antonio L.; Cunha, Ítalo; Loureiro, Antonio A. F.; Oliveira, Leonardo B. (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg), 2015)
Bilinear pairing has many applications in cryptography. Several IDbased, and also attribute-based cryptosystems were proposed using bilinear pairings of algebraic curves. This work aims at presenting the principal pairingbased cryptography toolkits, comparing their main characteristics as optimization, readability and coverage. This paper also contemplates an evaluation of the performance and energy efficiency of each of them and their cryptoprimitives, in order to define the pros and cons of each toolkit.